Two levels of decision-making in receiving international search and rescue teams. Issue 8 (16th November 2020) - Okita, Yosuke; Shaw, Rajib
ABSTRACT: In recent years, many international search and rescue (SAR) teams have been deployed to large-scale disasters across state borders. However, previous lessons show that, in some cases, the affected countries received unnecessary, unqualified, or too many teams, resulting in further burdens on them. The practical note aims to provide a model for decision-making for affected governments in receiving international SAR teams. Decision-making occurs on two levels: whether to receive international SAR teams, and how to limit the number of incoming teams.